The Experiences of Criminalized Women When Accessing Health Care Services During Incarceration Within Provincial Jails: A Critical Narrative Study - Zendo, Shamiram (2015)
Abstract There has been a noticeable increase in the imprisonment of women in Canada, within the last 20 years. The purpose of this critical inquiry was to capture and promote the voices and stories of criminalized women, in order to serve their interest. Five individual in-depth interviews were conducted with women, who were incarcerated in provincial jail. A critical paradigm was used to explore how socioeconomic and gender inequalities, embedded in the social, political, and historical contexts, influenced criminalized women’s experiences when accessing health care. The findings of this study described how criminalized women experience fragmentation in health care access, which encouraged the women to engage in sharing of illicit drugs. Furthermore, the study findings illustrated that neo-liberal policies have negatively influenced the criminalized women’s ability to self-care